Therapy of human T-cell acute lymphoblastic leukaemia with a combination of anti-CD7 and anti-CD38-SAPORIN immunotoxins is significantly better than therapy with each individual immunotoxin - Flavell, D J (Nature Publishing Group, 2001)
Severe combined immunodeficient (SCID) mice injected i.v. with the human T-ALL cell line CCRF CEM (SCID-CEM mice) develop within 50 days life-threatening multi-organ growth of leukaemia cells. The development of leukaemia in SCID-CEM mice treated with three 10 μg i.v. doses of the anti-CD7 immunotoxin (IT) HB2-SAPORIN or the anti-CD38 IT OKT10-SAPORIN was significantly delayed compared with PBS sham-treated animals but 90% of animals treated with either IT eventually developed disseminated leukaemia cell growth. In contrast treatment of SCID-CEM mice with a combination of both ITs led not only to a significantly greater delay in time to leukaemia development but also in the numbers of animals remaining leukaemia free (60%). The native HB2 and OKT10 antibodies (both murine IgG (1) antibodies) exerted significant, though relatively weak therapeutic effects, probably mediated through an antibody-dependent cellular cytotoxicity (ADCC) mechanism. Moreover, there was no in vivo additivity of therapeutic effect when both antibodies were used in combination. Apparent, however, was that the combination of HB2-SAPORIN IT with OKT10 antibody led to an intermediate therapeutic effect that was significantly greater than that obtained when either was used alone but significantly less than that obtained when the two IT combination was utilized. This was similarly the case for the combination of OKT10-SAPORIN IT with HB2 antibody though the effect was less pronounced in this instance. This result suggests that the therapeutic effect of IT + antibody treatment results from an additivity between antibody-mediated delivery of saporin combined with a SCID mouse NK cell-mediated ADCC attack on the target cell directed through target cell bound antibody Fc engagement with FcγRIII on the NK cell surface. The combination of both ITs however gave the best therapeutic outcome in SCID-CEM mice probably as the result of (i) delivery of greater amounts of saporin to target CEM cells positive for both CD7 and CD38, (ii) delivery of an effective dose of saporin to CEM cells downregulated or negative for one of the target antigens and (iii) through ADCC mechanisms that interact additively with IT action. We have previously proposed that combination IT therapy would be one means of overcoming the problem of heterogeneity of antigen expression within a global tumour cell population and these additional findings support this and provide a further strengthening of the rationale for employing cocktails of ITs for the treatment of human malignancies. © 2001 Cancer Research Campaign http://www.bjcancer.com